Milo head silage (Milage) rations for finishing yearling steers - Bolsen, K.K.; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Four finishing rations evaluated in the l02-day trial were: (1) unprocessed (Whole) milage, (2) processed (rolled) silage, (3) processed milage plus high moisture milo and (4) high-moisture milo plus chopped hay. Approximate roughage levels were 24% in rations 1 and 2 and 15% in rations 3 and 4. Yearling steers fed processed milage plus high--moisture llIilo gained faster (P<.05) and more efficiently (P<.05) than steers fed any of the other three rations. Steers receiving Whole milage (ration 1) consumed 9.4% more feed (P<.05) and required 14.0% more feed per lb. of gain than steers receiving rolled milage (ration 2). Steers fed rolled milage (rations 2 and 3) required an average of 15.8 and 8.52%, respectively, less grain per lb. of gain than steers fed rations 1 and 4.
Keywords: Beef; Milo silage; Yearling steers; Milage